2003
DOI: 10.1103/physrevb.67.134101
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced changes in protactinium metal: Importance to actinide-metal bonding concepts

Abstract: Protactinium occupies an important position in the actinide series of elements, as it represents the first of four elements ͑Pa-Pu͒ having 5 f -electron character in their bonding at atmospheric pressure. We have determined in experimental studies with synchrotron radiation to 130 GPa, that the tetragonal structure of protactinium ͑space group I4/mmm) converts to an orthorhombic, alpha-uranium structure ͑space group Cmcm͒ at 77͑5͒ GPa, where the atomic volume has been reduced by ϳ30%. This structural change is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…3 lends support to the latter explanation. That the 5 f electrons are not fully itinerant in α -Pu is in conformity with its lower value (42GPa) of the bulk modulus [16], compared with the measured bulk modulus of 104 GPa in α -U [8], ~ 118 GPa in Pa-II with α -U structure [7] and ~ 100 GPa for Am IV [9]. It is also consistent with the recent measurements of electronic heat capacities which show that α -Pu is a heavy fermion metal ( having a value 17 for electronic specfic heat coefficient (γ) , the largest so far observed for a pure element ) having in it strong f-f-correlations [17].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…3 lends support to the latter explanation. That the 5 f electrons are not fully itinerant in α -Pu is in conformity with its lower value (42GPa) of the bulk modulus [16], compared with the measured bulk modulus of 104 GPa in α -U [8], ~ 118 GPa in Pa-II with α -U structure [7] and ~ 100 GPa for Am IV [9]. It is also consistent with the recent measurements of electronic heat capacities which show that α -Pu is a heavy fermion metal ( having a value 17 for electronic specfic heat coefficient (γ) , the largest so far observed for a pure element ) having in it strong f-f-correlations [17].…”
supporting
confidence: 70%
“…occur, so far, in rare earths, Ce, Pr, Nd and the actinide, Pa [6][7][8]. A distorted form of this, in space group, Pnma with 4 atoms at 4c sites (+/-( x,1/4,z)) occurs in Am from 16 GPa [9] and an alloy of AmCm from 46 GPa [10].…”
mentioning
confidence: 99%
“…Söderlind and Eriksson [36] studied the crystal structure of Pa and predicted a phase transition to a high-pressure face-centered orthorhombic phase very close to that of a-U. This was understood to be a consequence of a subtle pressure-induced increase of the 5f-band occupation in Pa, and the orthorhombic phase was later confirmed by diamond-anvil-cell experiments [37]. The detailed study of uranium by Akella et al [38] showed a very similar result, with DFT accurately reproducing both the ground-state crystal structure as well as its delicate changes with pressure.…”
Section: Now When We Have Confidently Established That Photoemission mentioning
confidence: 90%
“…The fcc to bct phase transition in Th was explained to be due to an increase of 5f-electron occupation with pressure [15]. Notably, in the case of Pa, calculations [16] predate experiment [18] by several years predicting a high-pressure orthorhombic phase (Cmcm, α-U-type.…”
Section: Early Actinides: Thorium Through Neptuniummentioning
confidence: 94%